Learning Analytics Framework for STEM Education: MERN Stack Implementation - Rani, Sandya; Shakthi, Uva (Journal of Research in Vocational Education, 2025)
The MSPHE is an online Web Application, App, and Software Application designed to improve the management of academic activities within educational institutions. It aims to provide administrators, educators, and students with a perceptive interface that facilitates interactions and manages data efficiently. To accomplish this, the system is created using a modern technology stack. The Frontend is developed with React.js, allowing a dynamic and responsive user experience, and Node.js and Express are utilized for the Backend, providing a server-side framework that handles requests and processes data efficiently. The database, MongoDB, provides scalable and adaptable data storage. Numerous capabilities are included in the AMS to support crucial operations. Such as Student and Faculty Data management, Attendance monitoring for students, monitoring student's marks, course management, event management, and mentorship tracking for monitoring students. A robust RESTful API provides access to these features, guaranteeing smooth front-end and back-end interactions.